Значення Кінбурнської коси в збереженні орлана-білохвоста в зимовий період - Петрович, З.О.; Редінов, К.О. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2007)
Observations were taken over the period 1993-2006 in the Dnieper Delta, on Kinburnskiy Peninsula, Dnepro-Bugskiy, Berezanskiy and Tiligul'skiy Limans, in Yagorlytskiy and Tendrovskiy Bays, along the coast of the Black Sea and adjacent agricultural landscapes. First individuals in areas of winter assemblages appear in August, while dispersion is observed in February-March. 21-30 September 2002 on Kinburnskaya Spit it was found a dead White-tailed Eagle, ringed 27 May 2002 as a chick in Poland.